Coordinated Control of DC Microgrid System Based on Bus Voltage Stratification - Qiyou LIN; Wenliang JIANG; Yuanyuan LI; Dongdong WANG; Sinan MOU (Zhongguo dianli, 2022)
In a DC microgrid system, distributed units are usually connected to the DC bus in a decentralized manner, and distributed power sources and loads are easily affected by the external environment, which degrades the bus voltage stability of the DC microgrid. In order to solve this problem, a coordinated control strategy for DC microgrid system based on bus voltage stratification is proposed in this paper. The strategy builds a DC microgrid system structure mainly based on photovoltaic power generation, and then divides the bus voltage into five levels. Under the corresponding operation mode of each level, the operation mode and the control strategy are studied. Finally, the effectiveness of the proposed control strategy in suppressing the fluctuation of the system bus voltage is verified when the fluctuation of the photovoltaic power generation and the load is caused by the change of environmental factors.